2022
DOI: 10.3390/antiox11040693
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Biochemical and Molecular Response of Different Winter Wheat Varieties under Drought Stress at Germination and Seedling Growth Stage

Abstract: Due to climate change in recent years, there has been an increasing water deficit during the winter wheat sowing period. This study evaluated six Croatian winter wheat varieties’ physiological, biochemical, and molecular responses under two drought stress levels at the germination/seedling growth stage. Lipid peroxidation was mainly induced under both drought stress treatments, while the antioxidative response was variety-specific. The most significant role in the antioxidative response had glutathione along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 114 publications
3
25
0
Order By: Relevance
“…[ 17 ] in the case of the exposure of wheat cultivars to severe drought stress. Decreased CAT activity in some Croatian wheat cultivars subjected to drought stress was also observed recently by Vuković et al [ 57 ]. Although the aforementioned studies demonstrated a similar response of CAT activity in wheat subjected to drought stress as the present investigation, there are a few important methodological distinctions to keep in mind.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[ 17 ] in the case of the exposure of wheat cultivars to severe drought stress. Decreased CAT activity in some Croatian wheat cultivars subjected to drought stress was also observed recently by Vuković et al [ 57 ]. Although the aforementioned studies demonstrated a similar response of CAT activity in wheat subjected to drought stress as the present investigation, there are a few important methodological distinctions to keep in mind.…”
Section: Discussionsupporting
confidence: 77%
“…Namely, the studies cited earlier were conducted under growth chamber conditions while this study presents the results obtained under field growing conditions. Furthermore, the study by Vuković et al [ 57 ] examined the response of wheat seedlings to drought stress, while the main focus of the present study was set to the response of flag leaf as one of the main photosynthesis sites in wheat determining the grain filling rate and yield [ 39 ]. On the contrary to CAT, APX and especially GPOD showed a higher sensitivity to drought stress, which is not surprising taking into account the higher affinity of APX for H 2 O 2 compared to CAT [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress reduces the uptake of CO 2 and subsequently reduces carbon fixation, saturating the electron transport system and forming ROS which, in turn, promote oxidative stress and lipid oxidation [ 26 , 40 ]. As the first enzyme in the antioxidant system, SOD plays a crucial role in preventing oxidative damage [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a decrease in these enzymatic activities was found in wheat. Vuković et al [ 48 ] reported different response of CAT activity depending on the genotype-specific differences and on drought intensity. Authors suggested that the lack of CAT amplification boosted lipid peroxidation in the affected varieties.…”
Section: Discussionmentioning
confidence: 99%